Ethical Study on Imperative Politeness Islamic Education Among Students of Teaching And Education Faculty of State Islamic Institute - Muchammad Djarot (AT-TURATS, 2020)
This paper derived from the research results entitled the Ethical Study On Imperative Politeness Islamic Education Among Students Of Teaching And Education Faculty Of State Islamic Institute. The Research aims to get an overview of: The first, ethical perspective of Islamic education on the imperative of the imperatives in the interaction among students in the Faculty of Tarbiyah and the study of the school. This research used qualitative methods that obtain descriptive data of written or spoken words from people and behaviors observed. The data collection techniques used the methods of reading and capable methods. Data analysis techniques used pragmatic methods